Validation of an international classification of disease, tenth revision, clinical modification (ICD‐10‐CM) algorithm in identifying severe hypoglycaemia events for real‐world studies - Her, Qoua L.; Dejene, Sara Z.; Ismail, Sherin; Wang, Tiansheng; Jonsson‐Funk, Michele; Pate, Virigina; Min, Jea Young; Flory, James (Diabetes, obesity & metabolism, 2024)
Aim The transition to the ICD‐10‐CM coding system has reduced the utility of hypoglycaemia algorithms based on ICD‐9‐CM diagnosis codes in real‐world studies of antidiabetic drugs. We mapped a validated ICD‐9‐CM hypoglycaemia algorithm to ICD‐10‐CM codes to create an ICD‐10‐CM hypoglycaemia algorithm and assessed its performance in identifying severe hypoglycaemia. Materials and Methods We assembled a cohort of Medicare patients with DM and linked electronic health record (EHR) data to the University of North Carolina Health System and identified candidate severe hypoglycaemia events from their Medicare claims using the ICD‐10‐CM hypoglycaemia algorithm. We confirmed severe hypoglycaemia by EHR review and computed a positive predictive value (PPV) of the algorithm to assess its performance. We refined the algorithm by removing poor performing codes (PPV ≤0.5) and computed a Cohen's κ statistic to evaluate the agreement of the EHR reviews. Results The algorithm identified 642 candidate severe hypoglycaemia events, and we confirmed 455 as true severe hypoglycaemia events, PPV of 0.709 (95% confidence interval: 0.672, 0.744). When we refined the algorithm, the PPV increased to 0.893 (0.862, 0.918) and missed <2.42% (<11) true severe hypoglycaemia events. Agreement between reviewers was high, κ = 0.93 (0.89, 0.97). Conclusions We translated an ICD‐9‐CM hypoglycaemia algorithm to an ICD‐10‐CM version and found its performance was modest. The performance of the algorithm improved by removing poor performing codes at the trade‐off of missing very few severe hypoglycaemia events. The algorithm has the potential to be used to identify severe hypoglycaemia in real‐world studies of antidiabetic drugs.